Molecular Characterization of Salmonella Enteritidis Isolates by Pulsed Field Gel Electrophoresis and Plasmid Profiling - Loke, Chui Fung (1997)
Seventy Salmonella enteritidis isolates from poultry and 48 isolates from human sources were analyzed for their restriction polymorphism patterns generated by pulsed field gel electrophoresis (pFGE), plasmid profiles and antimicrobial susceptibility patterns. In the present study, PFGE analysis following digestion with two low-frequency-cleavage restriction endonucleases, XbaI (5'-TCTAGA-3') and SpeI (5'-ACTAGT-3') generated nine and five distinct fingerprints respectively with F values ranging from 0.06 to 0.97. Digestion with high-frequency-cleavage restriction endonucleases, M1uI (5'-ACGCGT-3') and Pvun (5'-CAGCTG-3') revealed less polymorphism in their PFGE patterns with more than 95% of the S. enteritidis isolates belonging to a single fingerprint. PFGE restriction analysis with Sail (5'-GTCGAC-3'), EcoRI (5'-GAATTC-3') and HindIII (5'-AAGCTT-3')revealed identical PFGE pattern (F value = 1). Thus, suggesting that these restriction endonucleases were not suitable in PFGE analysis of S. enteritidis. In plasmid profiling, five different plasmid profiles were obtained among the 1 16 plasmid-containing isolates, of which, plasmid profile of SE38 containing a single serotype-specific plasmid of 60 kb, was the most predominant (83.8%). A significant number of S. enteritidis isolates from both sources were resistant to p-Iactams antibiotic other than ampicillin, glycopeptides, polypeptide and sulphamethoxazole. The most common pattern encountered was PVaBSu. Resistance to aminoglycosides (gentamicin, kanamycin and streptomycin), quinoiones (nalidixic acid), cephalosporins and chloramphenicol was uncommon. Of the 118 isolates, 114 (96.5%) were resistant to at least four antimicrobial agents. Only one isolate from human was susceptible to all 12 antimicrobial agents but none of the isolates expressed resistance to 10 antimicrobial agents. The overall analysis of the present study revealed that PFGE was more suitable and of high discriminatory value in differentiating among S. enteritidis isolates than plasmid profiling and antimicrobial susceptibility testing. The similarities among S. enteritidis isolates from human and poultry sources, as determined on the basis of restriction polymorphism patterns, plasmid profiles and antimicrobial susceptibility patterns, might suggest a common origin of the S. enteritidis isolates and also the possible mode of transmission of S. enteritidis isolates from nonhuman sources to human beings.